Hepatocyte growth factor (HGF) in patients with acute brucellosis - Ozden, M; Kalkan, A; Demirdag, K; Kilic, SS; Denk, A; Yuce, P (Taylor & Francis as, 2004)
In this prospective study, we investigated the serum levels of hepatocyte growth factor (HGF) and C-reactive protein (CRP) before and after the treatment of patients with acute brucellosis. The study comprised 58 patients with acute brucellosis and 30 healthy volunteers. Pre-treatment serum HGF levels of 58 patients with acute brucellosis (1548.6 +/- 220.1) were significantly higher than levels of the control group (401.4 +/- 69.7) (p< 0.001). Serum levels of HGF and CRP significantly decreased at the end of the treatment period (p< 0.001). Post treatment, levels did not differ from those of the control group ( p > 0.05). Serum HGF levels of patients with acute brucellosis correlated to CRP and ALT levels ( r : 0.922, 0.752; p< 0.001, respectively). Our findings suggest that serum HGF levels may be used as a supplementary marker to evaluate the effectiveness of the treatment in patients with acute brucellosis.
Keywords: C-Reactive Protein; Serum; Purification; Pneumonia; Diseases; Failure; Injury; Plasma; Act